Pengaruh Komisaris Independen, Komite Audit Independen, Likuiditas dan Ukuran Perusahaan Terhadap Integritas Laporan Keuangan - Imaz Masriah; Iwan Setiadi (ITB Ahmad Dahlan Jakarta, 2020)
The purpose of this study is to prove the influence of corporate governance mechanisms,liquidity and company size on the integrity of financial statements in various industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2012-2018 period. The corporate governance mechanism in this study was measured by an independent commissioner and an independent audit committee. The sample of this study was 21 companies of various industry sectors which were listed on the Indonesia Stock Exchange (IDX) for the 2012-2018 period so that the total sample of this study was 147 samples. This research belongs to associative research (relationship). The sample selection uses a purposive sampling method. The values tested in this thesis use the formula of financial ratios and regression analysis. The results of this study indicate that independent commissioners and company size do not affect the integrity of financial statements. The Independent Audit Committee has a negative effect on the integrity of the financial statements.While liquidity (current ratio) has a positive effect on the integrity of financial statements.